Improving Energy Efficiency in Timisoara, Romania - Mot, Manuela (World Bank, Washington, DC, 2016)
The Tool for Rapid Assessment of City Energy (TRACE) is used for conducting rapid assessments of energy use in cities. It helps prioritize sectors with significant energy savings potential, and identifies appropriate energy efficiency interventions across six sectors-transport, municipal buildings, water and waste water, public lighting, solid waste, and power and heat. It is a simple, low-cost, user-friendly, and practical tool that can be applied in any socioeconomic setting. This report is based on the implementation of the TRACE tool in Timisoara in April 2013 and outlines ideas on what the city could further do to improve its energy efficiency performance. It details the analysis carried out and the recommendations derived as a result, for district heating maintenance and upgrade, non-motorized transport, public transport development, parking restraint measures, municipal buildings audit and retrofit, street lighting timing program, and active leakage of water and pressure management.